Web Based Tourism Object Information System in Madura - Rhaiza Syarkawi (International Journal of Science, Engineering, and Information Technology, 2017)
Madura is one of island in East Java that has four regency; those are Bangkalan, Sampang, Pamekasan and Sumenep. Madura was called Salt Island because it is one of the largest producer of salt in Indonesia. Madura is also famous of diversity culinary tours and beautiful tourism. This final project create information system that can be introducing Madura especially four regency in Madura. The introduction are tourism, hotel, the price of ticket in every tourism, the price of foods the history of Madura and pictures. Hopefully this information system can help tourists to get all of information about tourisms and hotels in Madura easily.